2008
DOI: 10.1089/tmj.2008.0001
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Diagnostic Confidence, and Management Concordance in Live-Interactive and Store-and-Forward Teledermatology Compared to In-Person Examination

Abstract: Teledermatology studies have examined diagnostic concordance between live-interactive (LI) and in-person examinations (IP); and between store-and-forward (SF) and IP examinations. However, no studies have looked simultaneously across all three care delivery modalities, and few have measured management concordance and diagnostic confidence of the dermatologist. The purpose of this study was to compare LI and SF modalities with IP with respect to diagnostic and management concordance and to compare physician dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 8 publications
4
77
0
5
Order By: Relevance
“…4 Three studies compared the two modes. 14,23,24 In one study, 23 patients were not seen in-person, while another found identical diagnoses with in-person for 64% of patients with greater agreement for live interactive than store-and-forward that was not statistically significant. 24 A third study showed combining methods significantly increases concordance with in-person exams.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…4 Three studies compared the two modes. 14,23,24 In one study, 23 patients were not seen in-person, while another found identical diagnoses with in-person for 64% of patients with greater agreement for live interactive than store-and-forward that was not statistically significant. 24 A third study showed combining methods significantly increases concordance with in-person exams.…”
Section: Introductionmentioning
confidence: 93%
“…14 Although live interactive and store-and-forward methods have been compared before 14,23,24 the studies comparing remote methods to in-person 14,24 used diagnoses of single inperson dermatologists. This study extends teledermatology research by directly comparing concordance between inperson, live interactive, and store-and-forward methods with two in-person dermatologists establishing a diagnostic comparison baseline, while also addressing confidence and biopsy decisions and effects of video quality in live interactive consultations.…”
Section: Introductionmentioning
confidence: 99%
“…Szá-mos klinikai kutatás vizsgálta a teledermatológia orvosi alkalmazásának megbízhatóságát [1,8,28,33,[34][35][36][37][38].…”
Section: A Diagnózisok Megbízhatóságaunclassified
“…A teledermatológiai módszerrel diagnosztizálható betegek esetén a diagnózis megbízha-tósága 90%-os volt. Edison és mtsai módszere szerint [34] minden pácienst háromszor vizsgáltak meg más-más orvosok: egyszer személyesen, egyszer store-andforward módszerrel és egyszer valós idejű konzultáció során. Azt tapasztalták, hogy a különböző orvosok által felállított store-and-forward telemedicina esetén 73%-os a diagnózis egyezése a személyes konzultációval, míg valós idejű konzultáció esetén ennél magasabb, mintegy 80%.…”
Section: A Diagnózisok Megbízhatóságaunclassified
“…Complete Diagnostic Agreement Partial Diagnostic Agreement (Tan et al, 2010) .75-.82 .83-.89 (Heffner et al, 2009) .69 - (Silva et al, 2009) .87-.92 .96-1.0 (Edison et al, 2008) .73 - (Ebner et al, 2008) . 71-.76 .90-.97 (Bowns et al, 2006) .55 - (Oakley et al, 2006) .53 .64 (Tucker & Lewis, 2005) .56 .68 (Baba et al, 2005) .75 - (Mahendran et al, 2005) .44-.48 .64-.65 (Du Moulin et al, 2003) .54 .63 (Eminovic et al, 2003) .41 .51 (Lim et al, 2001) .73-.85 .83-.89 (Taylor et al, 2001) .44-.51 .57-.61 (High et al, 2000) .64-.77 .81-.89 (Whited et al, 1999) .41-.55 .79-.95 (Lyon & Harrison, 1997) .89 - (Zelickson & Homan, 1997) .88 - (Kvedar et al, 1997) .61-.64 .67-.70 Table 2.…”
Section: Referencementioning
confidence: 99%